The Effect of Covid-19 on The Financial Performance of Indonesia’s Livestock Industry - Maghfira Puti Gaisani; Idqan Fahmi; Hendro Sasongko (Jurnal Manajemen & Agribisnis, 2021)
This study aims to analyze the impact of COVID-19 on the financial performance of Indonesia’s poultry industry companies. The samples used in this study were broiler farming companies of XYZ Group from September 2019 to August 2020. Financial performance is used as the dependent variable to see the effect of the independent on the dependent. The independent variables in this study are leverage, liquidity, revenue, profitability, firm size, and COVID-19. The analytical method used is descriptive analysis with a quantitative approach. In this study, a z-score test, regression test, and internal firm interviews supported the results. The results showed that there were indications of problems with the firm's financial health. COVID-19 does not significantly affect its financial performance, but several other factors influence it, namely revenue, profitability, and firm size. Several forms of strategies that can be formulated for companies are maintaining cash flow by extending the debt period and shortening accounts receivable to restore the firm's financial health. Then make efficiency in the cost of goods sold and improve operational cooperation to improve the firm's financial performance. Companies can also increase funding by obtaining additional capital from a holding company before financing from outside parties. Keywords: COVID-19, financial distress, financial performance, poultry business, return on asset